Health Status of Infants Delivered Using Cesarean Section and Instrumental Methods - Yu.V. Sorokolat; T.M. Klimenko; Ye.O. Golyuk (Zaslavsky O.Yu., 2013)
Until now, the question about differences in the nature of the features of structure of morbidity and its structure among children under one year who were born naturally and surgically remains debatable. The authors analyzed the health status of infants who were born in the city by Cesarean section or by using instrumental methods. The portion of operative delivery in 2008-2012 averaged 21.4 %, the frequency of the use of instrumental methods of obstetric aid - 4.9 %. Forceps gradually replaced the carrying of vacuum extraction as less traumatic method. There has been marked the association between mode of delivery and used instrumental methods and the structure of infant morbidity. The growth of congenital malformations and a consistently high level of morbidity due to intranatal pathology open further prospects for improving prenatal monitoring and tactics of obstetric aid.